Sistem Hukum Perkawinan Pada Negara Hukum Berdasarkan Pancasila - Tengku Erwinsyahbana (Jurnal Ilmu Hukum, 2012)
Marriage is included as basic needs (rights) of every human being, whose goal is to establish a family or household who are happy and eternal by Belief in God Almighty. The inclusion of elements of the phrase "Belief in God Almighty" within the meaning of marriage mentioned in Article 1 of Law no. 1 of 1974, indicating that the marriage can not be viewed simply as a matter of personal (individual), but must also be viewed as the legal relationship between a man and a woman in a household that has religious values ​​based on the Pancasila as a life philosophy of the Indonesian nation.